Risk Management Analysis of Qardhul Hasan Financing Model in Islamic Financial Institutions - Fadilah, Siti; Ustanti, Mira (International Journal of Multidisciplinary Research of Higher Education, 2024)
Qardhul hasan loans are loans that do not use collateral to obtain capital assistance to improve micro, small and medium enterprises to be more developed, without collateral there is a very large possibility of risk. This study aims to analyze the qardhul hasan financing procedure and the risk of qardhul hasan financing management in one of the Baitul Mal Wat Tamwil Nuansa Umat on the island of Java. Observations were made of the operational activities of Baitul Mal Wat Tamwil Nuansa Umat and customer activities to see the impact of financing. This research uses a type of qualitative field research. Data collection techniques are obtained through interviews, observation and domunentation. The data collection technique was carried out through interviews with four informants including the head of the Purwoharjo Branch, the Central Board of Directors, the financing department, and Loan customers. Data validity uses data triangulation. Data analysis techniques using Miles and Huberman techniques, namely data collection, data display, data condensation and conclusions. The results of the study reveal that the qardhul hasan financing procedure at Baitul Mal Wat Tamwil Nuansa Umat is designed to provide access to financing without collateral that is transparent and efficient with Forum Silaturahmi Anggota which functions as a social control mechanism to support the sustainability of payments.  In terms of risk management at Baitul Mal Wat Tamwil Nuansa Umat, it still needs to be improved. requires improvement to reduce the risk of many collectabilities and also arrears that occur, such as business bankruptcy, fraud, names used by others, defaults due to partners working outside the island or out of the country. The risk management process includes identifying, measuring, monitoring and controlling risks.